A single-center experience of parathyroidectomy in 1500 cases for secondary hyperparathyroidism: a retrospective study. Issue 1 (31st December 2022) - Zhao, Shasha; Gan, Wei; Xie, Wenjia; Cao, Jinlong; Zhang, Liang; Wen, Ping; Yang, Junwei; Xiong, Mingxia
Abstract: Background: Chronic kidney disease (CKD) is a global public health problem. With the deterioration of renal function, a certain proportion of CKD patients enter the uremic stage, and secondary hyperparathyroidism (SHPT) becomes a challenge. For refractory hyperparathyroidism, parathyroidectomy (PTX) plays a key role in reducing mortality and improving prognosis. Nevertheless, no consensus has been reached on the optimal surgical method. We aimed to provide evidence for the effectiveness of surgical treatment by summarizing the experience from our center. Methods: Clinical data from 1500 patients undergoing parathyroidectomy were recorded, which included 1419 patients in a total parathyroidectomy without autotransplantation (tPTX) group, 54 patients in a total parathyroidectomy plus autotransplantation (tPTX + AT) group, and 27 patients in the other group. Perioperative basic data, intact parathyroid hormone (i-PTH) levels, serum calcium levels, serum phosphorus levels, pathological reports, coexisting thyroid diseases, short-term outcomes and complications were analyzed. Moreover, postoperative complications were compared between the tPTX and tPTX + AT groups. Results: Parathyroid hormone, serum calcium and phosphorus levels decreased significantly post-surgery. Two patients died during the perioperative period. As the two most common complications, the incidences of severe hypocalcemia and hyperkalemia were 36.20% (543 cases) and 24.60% (369 cases), respectively. Pre-iPTH levels (OR = 1.001, 95% CI: 1.001–1.001, p < 0.01), serum alkaline phosphatase (ALP) levels (OR = 1.002, 95% CI: 1.001–1.002, p < 0.01) and the mass of excised parathyroid gland (OR = 3.06, 95% CI: 1.24–7.55, p = 0.02) were positively associated with postoperative severe hypocalcemia, while age and serum calcium were negatively associated with it. Pathological reports of resected parathyroid and thyroid glands indicated that 96.49% had parathyroid nodular hyperplasia, 13.45% had thyroid nodular hyperplasia, and 4.08% had thyroid papillary carcinoma. Conclusions: Parathyroidectomy is a safe and effective treatment for refractory secondary hyperparathyroidism. Severe hypocalcemia is the main complication, and coexistent thyroid diseases should never be neglected.